Unpacking Brand Imperialism in Bangladesh: Emerging Market Perspective - Yeasir Fahim, Ather; Mamun, Abdullah Al; Khushee, Dil Afrooz; Hossain, Arshadul; Chakma, Tozim; Hassan, Emam Mehede (Goodwood Publishing, 2022)
Purpose: The main purpose of this article is to understand the meaning of counterfeit consumption from less affluent consumers’ perspectives. Methodology A qualitative research process was taken as a means to conduct this study, and the data is collected using an ethnographic and ethnographic approach. An iterative hermeneutic process is followed to analyze the data collected. Results: The study revealed that less affluent people use counterfeit products mainly to reflect abhorrent sentiments toward foreign brands. This abhorrence leads to building resistance and resilience, which is primarily the production of counterfeit products. Limitations: The significance of this research paper can be limited by the respondent sample size, which was not so large for concluding. Moreover, the data were only collected from the respondents of Dhaka City because of its time limitation, which results in making our study narrow. Contribution: This study will help scholars and academicians as well as market researchers to get depth understanding of why counterfeit consumption is acceptable to less affluent consumers. And, this empirical study will also have detailed the perceptions of less affluent customers regarding the consumption of foreign brands. As no prior papers have discussed the different aspects of counterfeit consumption by less affluent consumers, this paper will add new insight into the topic of academia.